Child Health, Poverty and the Environment: The Canadian Context - Chaudhuri, Nita (Can J Public Health, 1998)
In Canada, there has been little research exploring the link between child poverty and exposure to environmental contaminants. However, children living in poverty are more likely to grow up in neighbourhoods adjacent to polluting industries and heavily used transportation corridors. They are also more likely to live in improperly designed or maintained buildings where levels of contaminants and toxic residuals may be high, and indoor air quality poor. Risk factors such as exposure to cigarette smoke and poor nutritional status, together with the above living conditions during growth and development, create conditions that make children living in poverty more vulnerable to the effects of environmental contaminants. In Toronto, the South Riverdale Community Health Centre is developing grassroots techniques to build awareness and protect citizens. Given the growing levels of child poverty in Canada and decreasing environmental protection, the author suggests increased community action and health research for use in advocating for appropriate policy changes. ELECTRONIC SUPPLEMENTARY MATERIAL: Supplementary material is available for this article at 10.1007/BF03405092 and is accessible for authorized users.